A Short Review on Role of Some Natural Herbs in the Treatment of Hypertension - Khatoon, Tania; Naskar, Angana; pal, Aditi; Datta, Kunal; Kumar, Devinder; Kaur, Gurpreet; Karmakar, Paramita; Pal, Ujjal (Asian Journal of Pharmaceutical Research and Development, 2022)
The medical term for elevated blood pressure is hypertension (HTN). It's harmful since it strains the heart and increases the risk of heart disease and stroke as well as atherosclerosis (hardening of the arteries). Congestive heart failure, renal damage, and blindness are all possible outcomes of HTN. Many adverse effects are commonly associated with traditional antihypertensives. For the most part, people in underdeveloped nations prefer herbal medicines for primary health care since they are more tolerable by the human body and have less adverse effects. A great deal of effort has been made over the last three decades to discover native plants that have hypotensive and antihypertensive medicinal properties. It has been established that some of these medicinal herbs have hypotensive and antihypertensive properties, whereas others have been discredited. In order to evaluate the efficacy and clarify the safety profile of such herbal treatments for their antihypertensive potential, additional scientific study must be conducted to combine ayurveda expertise with modern medicine.